Inputs of soluble aerosol-derived trace metals and nutrients to the Canary Basin. A study of factors that may influence bioavailability - López García, Patricia; Patey, Matthew David; Gelado Caballero, María Dolores; Hernández Brito, José Joaquín (2014)
African dust inputs have important effects on climate and the marine biogeochemistry of the subtropical North Atlantic Ocean. The impact of dust inputs on oceanic carbon uptake and climate is dependent on total dust deposition fluxes as well as the bioavailability of nutrients and metals in the dust. There are very few sets of long-term measurements of aerosol concentrations over the North Atlantic Ocean, yet such data is invaluable in quantifying atmospheric dust inputs to this important ocean region and critical for constraining biogeochemical models. In this work, we collected filters to calculate total suspended particle (TSP) concentrations continuously since 2002 and wet and dry deposition samples since 2004 in the island of Gran Canaria, Spain. Using soluble fractions of trace elements measured in this work, atmospheric deposition fluxes of soluble metals and nutrients are estimated. The influences in metal solubility due to the presence of acid components (like NO3− and SO24−) or ligands (like oxalate) as well as the dust load were also studied. Using the average of deposition flux at Tafira during 2004-2014 and considering that wet deposition is only 10% of the total flux, we were able to estimate the increase in dissolved trace metals and nutrients in the mixed layer during 1 year. These inputs of trace metals and nutrients seem to be significant relative to ambient concentrations in this area found in the literature, especially during the summer months when the water column is more stratified and nutrients inputs from deeper water are more limited. 475 475 1